How Celebrity Endorsement Influences Consumer’s Purchase Intention of Fashion Products on Instagram - Anthony Evan; Ario Adibratha Gunawan; Christie Anita Pardede; Felicia Hendra Wibowo; Ricky Noviyandi (Indonesian Business Review, 2021)
This purpose of this study is to assess the effectiveness of celebrity endorsement in marketing fashion products on social media in Indonesia. This study examines five attributes: familiarity, congruity, physical appearance, trustworthiness, and expertise. Research was conducted using the quantitative method with analytic observation and cross-sectional studies. Data obtained were managed descriptively and analytically using SPSS with multiple regression analysis. The result of our regression analysis showed three attributes that positively impact consumer’s purchase intention; familiarity with the celebrity, trustworthiness of the celebrity; and the expertise of the celebrity in giving recommendation. This quantitative study was conducted with a small number of samples, using a specific celebrity and product type. Studies using different celebrities and product categories may have different outcomes. Therefore, we cannot generalized the result of this study given the said limitation. This research was conducted to help management choose the right marketing tool and the best celebrity based on the result of this study to help management meet their marketing strategy objectives.